School active transportation planning and implementation: Exploring the perspectives of champions across Alberta, Canada. (December 2018) - Macridis, Soultana; McFadden, Kimberley; Johnston, Nora; Torrance, Brian; McEwan, Lesley
Abstract: Objective: The objective of this study was to understand school active transportation (AT) programming and implementation in diverse communities across the province of Alberta from the perspective of school AT champions who lead and facilitate the process. Methods: An online survey was administered through partner networks reaching province-wide between April 17 and May 17, 2017 with questions about: school demographics, years of active school AT programming, types of AT initiatives, and barriers and facilitators of AT planning and implementation. Key-informant interviews followed to elicit greater meaning to findings. Results: Twenty-one school AT champions completed the survey, of which 50% were teachers located in urban centres (51%) serving grades K-12 students. One-third of respondents were champions for ≥ 5 years. Champions formalized stakeholder committees comprised of: school staff, parents, students, and community traffic safety committees. Most undertook school AT planning activities, however only 23.8% reached implementation. Common barriers of planning and implementation included: insufficient support, distance, time, environment (e.g. weather), teacher turn-over, cost, perceived safety, and legal implications. Champions suggested areas for improvements including: municipal/provincial policy, promotional/educational materials, and volunteer recruitment. Conclusions: Findings demonstrate significant interest exists in school AT across Alberta. Champions are actively pursuing AT planning, but are experiencing a number of barriers in achieving successful implementation. Future directions include lobbying for greater financial support, educating champions and stakeholders on how to implement AT in their unique school setting, and finding ways to generate interest and enthusiasm for AT within school communities. The unique challenges of AT implementation in rural schools also need to be addressed. Highlights: Explored school active transportation champions' perspectives of implementation. Strategies across urban, suburban, rural, and remote contexts were discussed. Funding, policy, and educational support for school active transportation across settings were identified priorities. Involving students in planning enhanced active transportation uptake.